Relationship between emotional labor and job satisfaction: a study on preschool teachers - Mingmei, Yang; Pek, Lim Seong (International Journal of Evaluation and Research in Education (IJERE), 2024)
Teaching is a demanding profession that necessitates complex social and emotional skills. It has frequently been linked to negative outcomes such as tension, turnover, and job discontent. Every day, preschool educators interact with children and adults and must always maintain emotional control. This study aimed to examine the relationship between emotional labor and job satisfaction among preschool teachers. The study utilized a self-questionnaire; 280 first-line preschool teachers in Henan Province, Mainland, China, were selected to disseminate questionnaires. The overall mean score for emotional labor among preschool teachers was 3.90, indicating that these teachers are required to perform a great deal of emotional labor at work. Deep acting received the highest score, surface acting the second highest, and natural acting the lowest. There were considerable differences in emotional labor based on gender, kindergarten type, marital status, age, and job position. The correlation analysis revealed a significant positive relationship between preschool teachers’ emotional labor and job satisfaction. A regression analysis revealed that deep acting positively predicted job satisfaction by a mean of 28.4%.